Influencia de la formación practico profesional en el diseño de la malla curricular, de la carrera de trabajo social, Facultad de Ciencias Sociales de la Universidad Técnica de Machala, en el período 2013-2014. - Gómez Calero, Rosa Elena (2014)
Professional practical training the student is vital , envisions future professionals with relevance, prepared to face the challenges demanded by the profession in the occupational field within the region and the country with the ability to optimize resources and contribute to productivity -oriented development I longed for. Ensuring the inclusion of the multidisciplinary team of graduate professional futures as they are key to transform the collective demand for a response with quality and warmth part . Practical training is all as professional skills and abilities can generate and to address social issues . There is also the part of the professional readiness to face the challenges in all areas involving a social worker and competence in maintaining a balance between the purpose of intervention is in these cases , group and collective .